Istikhdām Wasīlah Kitāb Mufakkir Mumtiʽ fī Istiʽāb al-Mufradāt Lada Ţullab al- Madrasah al-Mutawassiţah al-Islāmiyah al-Manār - Fauziah, Rahmi Fitri; Rizal, Eka; Isra Hayati Darman (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The purpose of the research is to find out the use of fun thinker book media and to find out the effect of this media in mastery of vocabulary owned by students. The research method is quantitative research with experimental type, the research design used is Pretest-Posttest Control Group Design. tools for data collection are normality test, homogeneity test, and hypothesis testing. The use of fun thinker book media has six steps. And the result of the study is that there is an effect of using fun thinker book media in mastering mufradat 34% The results of hypothesis testing using the independent simple t test method and significance (sig tailed) 0.000 is small than 0.05 and the value of t count 4675 is greater than t table 2012. Then Ha: accepted, and H0: rejected.